2018
DOI: 10.1002/hbm.23974
|View full text |Cite
|
Sign up to set email alerts
|

Response selection codes in neurophysiological data predict conjoint effects of controlled and automatic processes during response inhibition

Abstract: The inhibition of prepotent responses is a requirement for goal-directed behavior and several factors determine corresponding successful response inhibition processes. One factor relates to the degree of automaticity of pre-potent response tendencies and another factor relates to the degree of cognitive control that is exerted during response inhibition. However, both factors can conjointly modulate inhibitory control. Cognitive theoretical concepts suggest that codings of stimulus-response translations may un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 57 publications
(115 citation statements)
references
References 62 publications
(147 reference statements)
15
99
0
1
Order By: Relevance
“…This process occurred approximately 100 ms later than processes reflected by the P1 in the S-cluster. The C-cluster has previously been found to be associated with response selection and control processes in the N2 time window (Chmielewski et al, 2018;Mückschel et al, 2017), which is in line with theoretical considerations suggesting that the N2 reflects intermingled perceptual and response-related (selection) processes (Folstein & Van Petten, 2008). The effect observed for the C-cluster was associated with the anterior cingulate cortex (BA24, BA32).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This process occurred approximately 100 ms later than processes reflected by the P1 in the S-cluster. The C-cluster has previously been found to be associated with response selection and control processes in the N2 time window (Chmielewski et al, 2018;Mückschel et al, 2017), which is in line with theoretical considerations suggesting that the N2 reflects intermingled perceptual and response-related (selection) processes (Folstein & Van Petten, 2008). The effect observed for the C-cluster was associated with the anterior cingulate cortex (BA24, BA32).…”
Section: Discussionsupporting
confidence: 81%
“…Previous findings have shown that the N2 reflects intermingled perceptual and response-related (selection) processes (Folstein & Van Petten, 2008). Using RIDE it was recently shown that these intermingled coding levels in the N2 are reflected by the S-cluster and the C-cluster (Chmielewski, Mückschel, & Beste, 2018;Mückschel et al, 2017). If the modulation of response selection processes is the most important factor underlying processes to overcome backward inhibition in adolescents compared with adults, it is likely that the above hypothesized effects for the N2 will be evident in the C-cluster data in the N2 time window.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As pointed out in previous studies, exogenous components (like the P1 or N1) are more closely time locked to stimulus onsets, whereas later endogenous components, are more variable in latency (Ouyang, Schacht, Zhou, & Sommer, 2013). In fact, it has been shown several times that processes occurring later in time-processes that reflected by the C-cluster-show considerable differences to original ERP data (Bluschke, Chmielewski et al, 2017;Chmielewski et al, 2018;Mückschel, Chmielewski et al, 2017;Ouyang, Hildebrandt, Sommer, & Zhou, 2017;Ouyang, Sommer, & Zhou, 2015b). In fact, it has been shown several times that processes occurring later in time-processes that reflected by the C-cluster-show considerable differences to original ERP data (Bluschke, Chmielewski et al, 2017;Chmielewski et al, 2018;Mückschel, Chmielewski et al, 2017;Ouyang, Hildebrandt, Sommer, & Zhou, 2017;Ouyang, Sommer, & Zhou, 2015b).…”
Section: S-clustermentioning
confidence: 83%
“…As outlined in Section 1, we perform RIDE according to established protocols (Verleger, Metzner, Ouyang, Śmigasiewicz, & Zhou, 2014) and the RIDE toolbox (manual available on http://cns.hkbu.edu.hk/RIDE.htm) to account for intraindividual variability in the data (Ouyang et al, 2011) and to dissociate between different coding levels that are otherwise intermingled in classical ERP components (Chmielewski, Mückschel, & Beste, 2018;Mückschel, Chmielewski et al, 2017). Mathematical details on the RIDE method can be found in Ouyang et al (2011).…”
Section: Residual Iteration Decompositionmentioning
confidence: 99%